Effects of Lactobacillus acidophilus NCFM on insulin sensitivity and the systemic inflammatory response in human subjects - Andreasen, Anne Sofie; Larsen, Nadja; Pedersen-Skovsgaard, Theis; Berg, Ronan M. G.; Møller, Kirsten; Svendsen, Kira Dynnes; Jakobsen, Mogens; Pedersen, Bente Klarlund (British journal of nutrition, 2010)
According to animal studies, intake of probiotic bacteria may improve glucose homeostasis. We hypothesised that probiotic bacteria improve insulin sensitivity by attenuating systemic inflammation. Therefore, the effects of oral supplementation with the probiotic bacterium Lactobacillus acidophilus NCFM on insulin sensitivity and the inflammatory response were investigated in subjects with normal or impaired insulin sensitivity. In a double-blinded, randomised fashion, forty-five males with type 2 diabetes, impaired or normal glucose tolerance were enrolled and allocated to a 4-week treatment course with either L. acidophilus NCFM or placebo. L. acidophilus was detected in stool samples by denaturating gradient gel electrophoresis and real-time PCR. Separated by the 4-week intervention period, two hyperinsulinaemic–euglycaemic clamps were performed to estimate insulin sensitivity. Furthermore, the systemic inflammatory response was evaluated by subjecting the participants to Escherichia coli lipopolysaccharide injection (0·3 ng/kg) before and after the treatment course. L. acidophilus NCFM was detected in 75 % of the faecal samples after treatment with the probiotic bacterium. Insulin sensitivity was preserved among volunteers in the L. acidophilus NCFM group, whereas it decreased in the placebo group. Both baseline inflammatory markers and the systemic inflammatory response were, however, unaffected by the intervention. In conclusion, intake of L. acidophilus NCFM for 4 weeks preserved insulin sensitivity compared with placebo, but did not affect the systemic inflammatory response.